Effect of Drying Air Flow Rate and Temperature on the Yield and Quality of Egg Flour of Purebred Chicken with Spray Dryer: Pengaruh Laju Alir dan Suhu Udara Pengering terhadap Kualitas dan Perolehan Tepung Telur Ayam Ras dengan Pengering Semprot - Haryono; Solihudin; Dayu Kusuma, Hersandy (Jurnal Kimia dan Rekayasa, 2025)
Protein is one of the food macronutrients that is really needed by the human body. Potential sources of food protein that are familiar to the public include chicken eggs, especially purebred chicken eggs. This fact can be estimated from the total need for purebred chicken eggs for household consumption in Indonesia. In 2023, the total need for these breeds of chicken eggs will reach 1.86 million tons. However, eggs in general are relatively unable to withstand damage to their nutritional value for long. Therefore, an effort is needed to process eggs into derivative food products so that they last longer, but still maintain their nutritional value. One of these businesses is processing eggs into egg flour through a drying process. Various types of dryers can be used to process eggs into egg flour. Spray dryers have relatively many advantages compared to other types of dryers. This research aims to determine the optimum conditions, including flow rate and drying air temperature, in the process of making egg flour from purebred chicken eggs using a spray dryer. Optimum drying conditions are determined based on the quality and yield of egg flour. Research methods include egg and dryer preparation, drying (making egg flour), quality analysis (protein and water content), and determining the yield of egg flour. The research results showed that the optimum conditions for making egg flour using a spray dryer were achieved when using drying air at a flow rate of 63.3 L/minute and a temperature of 66 °C. Under these drying conditions, egg flour was obtained with a protein content of 47.21%, a water content of 8.57%, and a yield of 27.54%. AbstrakProtein merupakan salah satu makronutrien pangan yang sangat dibutuhkan oleh tubuh manusia. Sumber protein pangan potensial dan akrab di masyarakat diantaranya adalah telur ayam, khususnya telur ayam ras. Fakta tersebut dapat diperkirakan dari total kebutuhan telur ayam ras untuk konsumsi rumah tangga di Indonesia. Pada tahun 2023, total kebutuhan telur ayam ras tersebut mencapai 1,86 juta ton. Namun demikian telur pada umumnya relatif tidak bisa tahan lama dari kerusakan nilai gizinya. Oleh karena itu diperlukan suatu usaha untuk mengolah telur menjadi produk pangan turunan agar lebih tahan lama, namun dengan tetap mempertahankan nilai gizinya. Salah satu usaha tersebut adalah mengolah telur menjadi tepung telur melalui proses pengeringan. Berbagai tipe pengering dapat dimanfaatkan untuk mengolah telur menjadi tepung telur. Pengering tipe semprot (spray dryer) memiliki relatif banyak keunggulan dibandingkan tipe pengering lainnya. Penelitian ini bertujuan untuk menentukan kondisi optimum, meliputi laju alir dan suhu udara pengering, dalam proses pembuatan tepung telur dari telur ayam ras dengan pengering semprot. Keoptimuman kondisi pengeringan ditentukan berdasarkan kualitas dan yield tepung telur. Metode penelitian meliputi penyiapan telur dan alat pengering, pengeringan (pembuatan tepung telur), analisis kualitas (kadar protein dan air), dan penentuan perolehan tepung telur. Hasil penelitian menunjukkan bahwa kondisi optimum pembuatan tepung telur dengan pengering semprot dicapai pada penggunaan udara pengering pada laju alir 63,3 L/menit dan suhu 66 °C. Pada kondisi pengeringan tersebut diperoleh tepung telur dengan kadar protein 47,21%, kadar air 8,57%, dan yield 27,54%